Studies on Optimization of Fly Ash, GGBS and Precipitated Silica in Geopolymer Concrete - Anilkumar; K S Sreekeshava; C Bhargavi (Construction Materials, 2025)
Considering the urgent need for sustainable construction materials, this study investigates the mechanical and microstructural responses of novel hybrid geopolymer concrete blends incorporating Fly Ash (FA), Ground Granulated Blast Furnace Slag (GGBS), Cement (C) and Precipitated Silica (PS) as partial replacements for traditional cementitious materials. The motive lies in reducing CO2 emissions associated with Ordinary Portland Cement (OPC). The main aim of the study was to optimise the proportions of industrial wastes for enhanced performance and sustainability. The geopolymer mixes were activated using a 10 M sodium hydroxide (NaOH)—Sodium Silicate (Na2SiO3) solution and cast into cubes (100 mm), cylinders (100 mm × 200 mm) and prism specimens for compressive, split tensile and flexural strength testing, respectively. Six combinations of mixes were studied: FA/C (50:50), GGBS/C (50:50), FA/C/PS (50:40:10), FA/GGBS/PS (50:40:10), GGBS/C (50:50) and GGBS/FA/PS (50:40:10). The results indicated that the blend with 50% FA, 40% GGBS and 10% PS exhibited higher strength. Mixes with GGBS and PS presented a l0 lower slump due to rapid setting and higher water demand, while GGBS-FA-cement mixes indicated better workability. GGBS/C exhibited a 24.6% rise in compressive strength for 7 days, whereas FA/C presented a 31.3% rise at 90 days. GGBS/FA mix indicated a 35.5% strength drop from 28 days to 90 days. SEM and EDS analyses showed that FA-rich mixes had porous microstructures, while GGBS-based mixes formed denser matrices with increased calcium content.